2021
DOI: 10.15252/embr.202051532
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial Ca 2+ uptake regulator, MICU1, is involved in cold stress‐induced ferroptosis

Abstract: Ferroptosis has recently attracted much interest because of its relevance to human diseases such as cancer and ischemiareperfusion injury. We have reported that prolonged severe cold stress induces lipid peroxidation-dependent ferroptosis, but the upstream mechanism remains unknown. Here, using genome-wide CRISPR screening, we found that a mitochondrial Ca 2+ uptake regulator, mitochondrial calcium uptake 1 (MICU1), is required for generating lipid peroxide and subsequent ferroptosis under cold stress. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…It is widely known that MMP controls adenosine triphosphate (ATP) synthesis and ROS generation and is itself controlled by the mitochondrial tricarboxylic acid cycle and respiratory chain. 60 In theory, both enhanced ATP synthesis and increased leakage of mitochondrial ROS from the respiratory chain lead to MMP hyperpolarization. Experimentally, chemiluminescence-based ATP measurements revealed that, for HCT-116 cells that were pretreated with Ru( ii )@COF-V for 2 h, cysteine depletion caused by exposure to a blue LED significantly reduced intracellular ATP.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely known that MMP controls adenosine triphosphate (ATP) synthesis and ROS generation and is itself controlled by the mitochondrial tricarboxylic acid cycle and respiratory chain. 60 In theory, both enhanced ATP synthesis and increased leakage of mitochondrial ROS from the respiratory chain lead to MMP hyperpolarization. Experimentally, chemiluminescence-based ATP measurements revealed that, for HCT-116 cells that were pretreated with Ru( ii )@COF-V for 2 h, cysteine depletion caused by exposure to a blue LED significantly reduced intracellular ATP.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of mitochondrial Ca 2+ signaling promotes cystine addiction and sensitizes PDAC cells to ferroptosis (Nakamura et al, 2021). However, there was no report on the specific mechanism of mitochondrial Ca 2+ imbalance-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ER-to-mitochondrion Ca 2+ transfer via MAMs is involved in apoptosis regulation [ 126 ]. Similarly, mitochondrial Ca 2+ uptake regulator 1 (MICU1) was found to regulate cold stress-induced ferroptosis in A549 cells [ 127 ]. Despite the paucity of research on MAMs and ferroptosis, Ca 2+ release from the ER into the cytoplasm increases during ferroptosis [ 95 ].…”
Section: Role Of Different Organelles In Apoptosis and Ferroptosismentioning
confidence: 99%